The distributive implications of patents on indivisible goods - Dan Usher (Queen's University, Department of Economics, 2004)
An indivisible good is an ideal type with interesting properties and strong implications about public policy. It is a good - such as a heart transplant or a treatment for AIDS - that must be consumed in a fixed amount or not at all. The community's demand curve for an indivisible good is a rotation of the distribution of income. Monopolization of ordinary goods can be expected to reduce everybody's consumption; monopolization of indivisible goods knocks out low income consumers. Deadweight loss from monopolization has a distinct distributional aspect best captured in a utility-weighted measure. Indivisible goods are strong candidates for public provision and for the expropriation of patents.
Keywords: D11; D42; H42; L12; O31; 330; patents; socialization; monopoly; deadweight loss; income distribution